Clinical indications for image-guided interventional procedures in the musculoskeletal system: a Delphi-based consensus paper from the European Society of Musculoskeletal Radiology (ESSR)-part I, shoulder - Sconfienza, Luca Maria; Adriaensen, Miraude; Albano, Domenico; Allen, Georgina; Aparisi Gómez, Maria Pilar; Bazzocchi, Alberto; Beggs, Ian; Bignotti, Bianca; Chianca, Vito; Corazza, Angelo; Dalili, Danoob; De Dea, Miriam; et al. (Springer Science and Business Media LLC, 2020)
Image-guided interventional procedures around the shoulder are commonly performed in clinical practice, although evidence regarding their effectiveness is scarce. We report the results of a Delphi method review of evidence on literature published on image-guided interventional procedures around the shoulder with a list of clinical indications.
Keywords: Interventional radiology; Shoulder; Ultrasonography; Injections; Platelet-rich plasma